PERANCANGAN PROMOSI D’DHAVE HOTEL MELALUI RE-DESAIN BROSUR - DESMEMI, Dr. Budiwirman, M.Pd, Dra. Jupriani, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
d'Dhave hotel established on October 9, 2010 is located at Jl. No. 1v Purus. 12 A Padang. d'Dhave hotel has been doing media promotion through brochures, business cards, letterheads and social media such as facebook. after seeing a media campaign in the form of a brochure which is owned by the hotel d'Dhave the authors are interested in me re-design before brochure because they lack the full information contained in this brochure required by consumers.The purpose of the design to give inform the target audience about the existence d'Dhave hotels, facilities, services, etc., and designing the good medium that is easy to understand and be understood by the target audience.the method analysis Data used in which the usefulness of SWOT analysis SWOT analysis is to observe and analyze the extent to which strengths, weaknesses, opportunities and threats that exist in the company.The results achieved are designing a good media campaign and effectively so that the message can be understood by the target audience, as well as informing about the existence d'Dhave hotels so that the target audience can use the services offered by the hotelKeywords: Design, Promotion, d'Dhave Hotel, Brochure